Crecimiento industrial y financiero: causalidad y políticas comparadas entre México, Brasil y Corea del Sur, 1970-2013 - Bollain Parra, Esteban (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The purpose of this study is to investigate the existence of the causal link between industrial growth and the expansion of credit to the non-financial private sector in three emerging economies: Mexico, Brazil and South Korea, in the period 1970 2013. The policy implemented by each country in its industrialization and financing productive sectors was analyzed before and after the period of financial liberalization were compared. The results of Johansen cointegration (1988) showed the existence of cointegration between the two variables. By applying the Granger causality analysis (1969, 1980), a causal unidirectional Granger ranging from industrial growth to the expansion of credit to the nonfinancial private sector in the three economies were found. Thus, it is shown that industrial growth is driving the financial development and not and not the other, as suggested by the orthodox theory. Results suggest measures greater state intervention to regulate and promote the industrial and financial sector dynamism. Therefore, the implementation of public policies could be a viable option for carrying out this process, generating a further boost to economic growth

El propósito del presente estudio es investigar la existencia de la causalidad entre el crecimiento industrial y la expansión del crédito hacia el sector privado no financiero en tres economías emergentes: México, Brasil y Corea del Sur, en el periodo 1970-2013. Para ello se compararon las políticas instrumentadas por cada país en sus procesos de industrialización y financiamiento al sector productivo antes y después del periodo de liberalización financiera. Los resultados de cointegración de Johansen (1988) mostraron la existencia de cointegración entre las dos variables. Mediante la aplicación del análisis de causalidad de Granger (1969, 1980), se encontró una relación de causalidad de Granger unidireccional que va desde el crecimiento industrial a la expansión del crédito al sector privado no financiero en las tres economías. Así, se muestra que es el crecimiento industrial el que impulsa el desarrollo financiero y no al contrario, como lo plantea la teoría ortodoxa. Los resultados sugieren medidas de mayor intervención del Estado para regular y promover el dinamismo industrial y del sector financiero. Para tal fin, la aplicación de políticas públicas se convierte en una alternativa viable para llevar a cabo ese proceso.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Políticas Públicas
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2014-1447; Causalidad; Crecimiento industrial; Políticas públicas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/986